Body mass Index does not impact long-term survival of patients with idiopathic pulmonary fibrosis undergoing lung transplantation - Lushaj, Entela B.; DeCamp, Malcolm M.; Maloney, James; Leverson, Glen; De Oliveira, Nilto; McCarthy, Daniel (Frontiers in Transplantation, 2023)
Objective: We investigated the impact of body mass index (BMI) on post-operative outcomes and survival of patients with interstitial pulmonary fibrosis (IPF) undergoing lung transplantation.We retrospectively reviewed 222 patients with IPF that underwent lung transplant (LT) at our institution from 2005-2019. Recipients were divided in 4 groups: group-1 consisted of underweight patients (BMI≤18.5kg/m 2 ), group-2 of normal weight patients (BMI 18.5-25kg/m 2 ), group-3 of over-weight patients (BMI 25-29.9kg/m 2 ) and group-4 of obese patients (BMI≥30kg/m 2 ).Group-1 consisted of 13 (6%) patients, group-2 of 67 (30%) patients, group-3 of 79 (36%) patients, group-4 consisted of 63 (28%) patients. Median BMI for group-1 was 17 (interquartile range [IQR]: 17, 18), for group-2 was 23 (22, 24), for group-3 was 29 (28, 29.5) and group-4 was 32 (31, 33). Patients in group-1 were significantly younger (p<0.01). Single LT comprised the majority of operation type in group-2 to group-4 and it was significantly higher than group 1 (p<0.01). Median follow-up time was 39 months (13-76). A total of 79 (35.5%) patients died by the end of study. Overall, five deaths occurred in group-1, 17 in group-2, 33 in group-3, and 24 in group-4. Kaplan-Meier analysis showed that mortality was not statistically significant between the groups (p=0.24). Cox-regression analysis was used to assess other possible risk factors that could influence the effect of BMI on mortality, including transplant type (single, double), lung allocation score, and age, diabetes and creatinine levels at surgery. None of these factors were shown to affect patient mortality (p>0.05). Overall reasons for death included graft failure (24%), infection (23%), respiratory failure (14%), and malignancy (13%).Conclusions: Body mass index does not impact long-term survival of patients with IPF undergoing lung transplantation.